Harvest times : IICA Canada: summary annual report 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
To encourage, promote and support our Member States in their efforts to achieve agricultural development and rural well-being through international technical cooperation of excellence. The Institute provides technical cooperation in its 34 Member States, where it addresses priority needs expeditiously in order to achieve increasingly inclusive, competitive and sustainable agriculture. Without a doubt, IICA’s most valuable asset is the close relationship it maintains with the beneficiaries of its work.